2013
DOI: 10.7860/jcdr/2013/7265.3783
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcome in Teenage Vs. Vicenarian Primigravidae - A Clinical Study

Abstract: It can be interpreted that teenage primigravidae had a significant number of complications in pregnancy, leading cause being anaemia, more preterm incidences and higher rates of LSCS, followed by higher number of NICU admissions. Since teenage pregnancy is a multifaceted problem, it demands multidimensional solutions. Teenage pregnancies are more common in populations with low socio-economic statuses, due to lack of education, awareness of complications of teenage pregnancies, and various other factors. Hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 7 publications
6
23
3
Order By: Relevance
“…Other researchers reported that anemia was noted in 68.7 % in teenagers [7]. Low iron stores common in these young women before pregnancy increase the risk of developing iron deficiency anemia during pregnancy which is influence by their insufficient dietary intakes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers reported that anemia was noted in 68.7 % in teenagers [7]. Low iron stores common in these young women before pregnancy increase the risk of developing iron deficiency anemia during pregnancy which is influence by their insufficient dietary intakes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Dias et al (2013) found that the normal vaginal deliveries are significantly higher and the LSCS rate is significantly lower in the teenage group than the adult group [7]. Conversely Goonewardene & Deeyagaha (2005) found there was no different in the mode of delivery between teenager and adult groups [9]. This variation in the finding may be attributable to the age and parity different in the control groups in both studies.…”
Section: Introductionmentioning
confidence: 58%
“…Therefore, the ability for the brain to plan, adapt to the social environment and to imagine possible future consequences of action or to appropriately gauge their emotional significance are still developing throughout adolescence. Numerous studies found, the preterm birth rate is significantly high among teenagers mothers [7] [8] [9]. On the other hand, the mode of delivery showed that different findings depend on the location of the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12.4% were multigravida among adolescent pregnancies while Padte et al 5 revealed no multipara in adolescent group. 7 Other studies also showed high rates of teenage mothers with anemia probably because of poor nutrition. 8,9 Inrapartum complications like Deep transverse arrest (100.0 vs. 0%), Non progress of labour (62.5 vs. 37.5) & foetal distress (66.6 vs. 33.4) were more in adolescent group which was statistically significant.…”
Section: Discussionmentioning
confidence: 99%